2013
DOI: 10.1021/ac303778j
|View full text |Cite
|
Sign up to set email alerts
|

Digital Electrophoresis of Charged Droplets

Abstract: A digital microfluidic system based on a direct electric charging and subsequent electrophoretic manipulation of droplets is made by simple fabrication at low cost. Digitally controlled two-dimensional droplet motions are realized by digital polarity control of an array of electrodes. By independent control of droplets and colorimetric detection, the coalescence and mixing of droplets is analyzed quantitatively. The gelation of sodium alginate and the crystallization of calcium carbonate by multiple droplet tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 36 publications
0
58
0
1
Order By: Relevance
“…에서 활발히 연구되고 있다 [1][2][3][4][5][6][7][8][9][10][11][12]. 액적 접촉충전 현상 기반의 미세 유체 기술은 개별 액적을 전기를 이용해 다루는 디지털 미세유체 기 술의 한 분야로 [13,14], 채널 내 액적을 다루는 액적 미세유체 (Droplet Microfluidics) [15,16] 기술과는 다르며 기존 미세유체 기술 들의 단점을 극복할 수 있어 새로운 대안 기술로 제시되고 있는 신 기술 이다 [17,18].…”
Section: 서 론 최근 새로운 미세유체 기술로써 액적 접촉충전 현상이 여러 분야unclassified
“…에서 활발히 연구되고 있다 [1][2][3][4][5][6][7][8][9][10][11][12]. 액적 접촉충전 현상 기반의 미세 유체 기술은 개별 액적을 전기를 이용해 다루는 디지털 미세유체 기 술의 한 분야로 [13,14], 채널 내 액적을 다루는 액적 미세유체 (Droplet Microfluidics) [15,16] 기술과는 다르며 기존 미세유체 기술 들의 단점을 극복할 수 있어 새로운 대안 기술로 제시되고 있는 신 기술 이다 [17,18].…”
Section: 서 론 최근 새로운 미세유체 기술로써 액적 접촉충전 현상이 여러 분야unclassified
“…Modeling of drop/particle motion experiencing the contact charging phenomenon is one of the key subjects in this field [4][5][6]66,[74][75][76][77][78][79][80][81][82]. In microfluidics field, the direct contact charging is used to manipulate droplet [38,[83][84][85][86] or particle motions [20,75] in microchannels in addition to digital microfluidic approaches [6,23,70,77,[87][88][89]. The details of each category will be covered in the following fundamentals and applications section.…”
Section: Historymentioning
confidence: 99%
“…Later, Im et al resolved this issue by decreasing system size and demonstrated various biochemical applications such as hydrogel and crystal formation as shown in Fig. 6 [23]. Because any conducting droplet can be handled by the ECD method as shown in Fig.…”
Section: Fundamentals and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Numerous studies [3][4][5][6][7][8][9][10][11][12][13] have reported various modes of droplet motion between electrodes using both experimental and numerical methods. A droplet behaves as an electrical charge-carrier between a pair of electrodes in an oil medium as an insulator.…”
Section: Introductionmentioning
confidence: 99%